Gender difference in the long-term impact of famine - Mu, Ren; Zhang, Xiaobo (International Food Policy Research Institute, 2008)
An increasing literature examines the association between restricted fetal or early childhood growth and the incidence of diseases in adulthood. Little is known, however, about gender difference in this association. We assess the impact of nutritional deficiency in the early lives of survivors of the Chinese Great Famine in terms of health and economic welfare, paying special attention to gender differences. We found evidence of several significant negative impacts for female -but not male-survivors, and the gender differences are statistically significant. Furthermore, we show that the selection bias caused by differences in mortality plausibly explains more than two-thirds of the documented gender difference in the long-term health of famine survivors.